Numerical study of high-power semiconductor lasers for operation at sub-zero temperatures. (6th March 2017) - Hasler, K H; Frevert, C; Crump, P; Erbert, G; Wenzel, H
Abstract: We present results on the impact of the Al-content in the waveguide structure on the electro-optical characteristics of 9xx nm, GaAs-based high-power lasers operated at room (300 K) and at sub-zero (200 K) heat sink temperatures. Experimentally a strong improvement of conversion efficiency and output power has been found if the lasers are cooled down. Numerical simulations using a software tool which solves the thermo-dynamic based drift-diffusion equations are able to reproduce the experimental findings. The reasons for the improved performance at lower temperatures are the enhancement of the modal gain and the reduced accumulation of electrons in the p-confinement layers resulting in a reduction of the leakage current. The latter allows the realization of lasers with a reduced Al content having a smaller series resistance and thus further enlarged conversion efficiency at sub-zero temperatures.